Variceal Veins Embolization and Left Renal Vein Stenting in a Patient with Combined Nutcracker and May–Thurner Syndrome - Aghdasi, Sina; Serati, Ali Reza; Moosavi, Jamal; Emami, Sepideh; Movahed, Mohammad Reza (International Journal of Angiology, 2021)
Nutcracker syndrome is defined as a compression of left renal vein leading to symptomatic hematuria and flank pain. There are very few reports about its association with May–Thurner syndrome that is related to compression of left iliac vein causing severe leg edema. We are reporting a rare case of a patient having both conditions successfully treated with sequential percutaneous interventions. This case and treatment options are discussed in detail.
Keywords: nutcracker syndrome; renal vein stenting; May–Thurner syndrome; stenting; flank pain; percutaneous interventions